Protected Designation of Origin as a Certified Quality System in the Andalusian olive oil industry: Adoption factors and management practices. (May 2015) - Parra-López, Carlos; Hinojosa-Rodríguez, Ascensión; Sayadi, Samir; Carmona-Torres, Carmen
Abstract: Protected Designation of Origin (PDO) is a Certified Quality System (CQS) that guarantees that there is a link between the particular characteristics of the production process of certain foodstuffs and their geographical origin. However, there is room for manoeuvre with regard to the management practices implemented when it comes to PDO. This paper investigates the factors related to and explaining the adoption of PDO in the Andalusian olive industry, the main olive growing region in the world, including an analysis of the varying characteristics of mill enterprises, managerial and supervisory staff, and of the differences and similarities between the practices implemented by PDO enterprises compared with the rest. A structured personal interview was held with the managerial and supervisory staff of 101 olive mill enterprises in the main olive growing provinces of Andalusia. The results show that CQS are not in general very widespread but that PDO is relatively prevalent. However no clear adoption factors for PDO have been identified, since the structural characteristics of enterprises adopting PDO and the personal characteristics, attitudes and opinions of their managers and supervisory staff are very similar to those not adopting it. The adoption of PDO seems to be explained by a contagion effect among industries that are located within less favourable, steeply sloping areas. Moreover, the adoption of PDO is not generally linked to an implementation of better industrial practices, rather of better marketing practices, since in general optimal industrial practices are already widespread in Andalusian olive mills. The policy and management implications of enhancing economic viability by increasing the spread of PDO, and by improving the practices implemented by PDO enterprises, are also discussed. Highlights: Quality certification can produce a competitive advantage for agro-food enterprises. PDO is a key quality strategy for the Andalusian olive oil industry. PDO adoption is more related to proximity than to the characteristics of enterprises and managers. Industrial practices are on average optimal and they are similar between PDO olive oil enterprises and the rest. Further developments in PDO marketing practices and organisation are required.